Increased systemic levels of inflammatory mediators following one‐stage full‐mouth scaling and root planing. (30th March 2018) - Morozumi, T.; Yashima, A.; Gomi, K.; Ujiie, Y.; Izumi, Y.; Akizuki, T.; Mizutani, K.; Takamatsu, H.; Minabe, M.; Miyauchi, S.; Yoshino, T.; Tanaka, M.; et al.
Abstract : Background and Objective: Full‐mouth scaling and root planing (FM‐SRP) acts as a potent inflammatory stimulus immediately after treatment; however, systemic inflammation typically improves in the long term. The contribution of FM‐SRP to systemic biological and acute‐phase responses is largely unknown. The purpose of this prospective intervention study was to assess the systemic and local biological responses after FM‐SRP. Material and Methods: Thirty‐one patients with generalized moderate‐to‐severe chronic periodontitis received 1‐stage FM‐SRP. Measurement of clinical parameters and body temperature as well as collection of subgingival plaque, peripheral blood and gingival crevicular fluid was performed before and after treatment 2 or 3 times. Quantification of periodontopathic bacteria in the sulcus and measurement of corresponding serum IgG titers were performed. Systemic and local inflammatory markers such as endotoxin, high‐sensitive C‐reactive protein (hs‐CRP) and 6 inflammatory cytokines were assessed using high‐sensitivity assays. Results: Compared to baseline values, FM‐SRP resulted in a substantial improvement in clinical parameters ( P < .05), lower bacterial counts ( P < .01) and a significant decrease of IgG titers against Porphyromonas gingivalis ( P < .001) 6 weeks after treatment. Comparing baseline parameters to those at 1 day post‐treatment, there was a statistically significant elevation in body temperature ( P = .007). In addition, a 5‐fold increase in hs‐CRP ( P < .001), a remarkable increase in interferon‐γ ( P < .001) and a slight increase in interleukin (IL)‐12p70 ( P = .001) were detected in serum samples. In the gingival crevicular fluid, marked increases in hs‐CRP ( P < .001), IL‐5 ( P = .001), IL‐6, IL‐12p70 and tumor necrosis factor‐α ( P < .001 for the latter 3 markers) were noted 1 day after treatment. Endotoxin levels were below measurable limits for most time points. Conclusion: FM‐SRP resulted in clinical and microbiological improvement 6 weeks post‐treatment, but produced a moderate systemic acute‐phase response including elevated inflammatory mediators 1 day post‐treatment.